PENJADWALAN PROYEK PEMBANGUNAN RUANG KELAS BARU SMK NEGERI 1 LUWUK MENGGUNAKAN METODE CRITICAL PATH METHOD - putu suartana; Sri Susilawati; Rizqi Novi Wulandari (Fakultas Teknik Universitas Tompotika Luwuk, 2025)
Project scheduling is one of the crucial aspects in project management. By conducting project scheduling, a better understanding of the relationships between each activity and the overall project can be obtained, allowing for the identification of activities that can be prioritized, activities that can be performed simultaneously, and activities that are interdependent. This research aims to identify the critical path and determine the duration of project completion using the Critical Path Method (CPM) for the construction project of the New Classroom Building at SMK Negeri 1, located at Jl. Ki Hajar Dewantara No. 17, KARATON, Luwuk District, Banggai Regency. The research method employed is a quantitative descriptive approach, involving the analysis and presentation of data in numerical form to objectively describe the project conditions. Primary and secondary data are used as the main sources of information in this study. The data analysis tool applied is the Critical Path Method (CPM), a network analysis technique (network planning) that functions to determine the critical path in project execution. The research results indicate that the critical path generated by the CPM scheduling method for the New Classroom Building Construction Project at SMK Negeri 1 Luwuk is through activities A-B-C-D-G-H-K-N-Q-R-W-AE-AF-AK-AP. Based on the calculations using the CPM method, the duration for completing the New Classroom Building Construction Project at SMK Negeri 1 Luwuk is 169 working days.